Methodological Approaches of Sampling Surveys for Examining the Beneficiaries of OP HRD 2014-2020 - Atanasov, Atanas; Kaloyanov, Todor (Research Papers, 2017)
The European Social Fund (ESF) is the main financial instrument of the European Union, which supports employment and rising education levels and skills of citizens. Bulgaria receives funding from the ESF Operational Programme "Human Resources Development" (HRD OP), which should contribute to the objectives in the field of employment and combating poverty and social exclusion.Verification of each individual item of expenditure and related evidence attached to the requests for payment to the beneficiaries, in practice it is almost unfeasible due to the large number of positions. One possible solution is to take the test only a part of the position. i.e. it is based on a sample of transactions.The purpose of this article is to present some methodological approaches to extract samples of administrative checks and spot checks to requests for reimbursement submitted by the beneficiaries of the operational program.The methodology provides selection via stratified sampling, which allow results to be spread across the entire population. For this purpose was developed post-stratification procedure. It creates the possibility to obtain estimates for the entire population (HRD OP), its sub-populations (strata) and for separate years.